Comparison of soil properties in urban and non‐urban grasslands in Budapest area. (31st August 2020) - Mónok, Dávid; Kardos, Levente; Pabar, Sándor Attila; Kotroczó, Zsolt; Tóth, Eszter; Végvári, György
Abstract: This study focused on the physical, chemical and microbiological characteristics of soils from different grasslands in the Budapest area. Our aim was to assess the influence of anthropogenic activities on these soils by comparing three types of site: urban, green‐urban and non‐urban. From these sites, a total of 72 topsoil samples were collected and analysed. The results indicated that many properties of soils varied greatly between the different types of site. Urban soils had significantly higher pH, carbonate and salt content, but smaller organic carbon content than the other soils. These differences could be explained in part by the greater artefact content, as the latter was significantly correlated with most of the main soil properties. Concentrations of the heavy metals measured (Co, Cu, Cr, Fe, Mn, Ni, Pb, Zn) were generally smaller in non‐urban soils. In urban and green‐urban soils, Cu, Cr, Ni and Pb levels were above the natural background levels, due to anthropogenic inputs in the city. Results of microbiological analyses were controversial. According to most probable number (MPN), there was no significant difference between types of site for bacterial and fungal numbers in soil. However, dehydrogenase activity and the number of bacterial cells were larger in non‐urban than in urban soils. It was also found that microbial parameters were influenced by many soil properties, for example organic matter and macronutrient (N, P, K) content of soils, the presence and amount of artefacts and metal concentrations in soil.